12-x=17-2x

Simple and best practice solution for 12-x=17-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-x=17-2x equation:


Simplifying
12 + -1x = 17 + -2x

Solving
12 + -1x = 17 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
12 + -1x + 2x = 17 + -2x + 2x

Combine like terms: -1x + 2x = 1x
12 + 1x = 17 + -2x + 2x

Combine like terms: -2x + 2x = 0
12 + 1x = 17 + 0
12 + 1x = 17

Add '-12' to each side of the equation.
12 + -12 + 1x = 17 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 17 + -12
1x = 17 + -12

Combine like terms: 17 + -12 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 10k-18=32 | | 30x^3+92x^2+70x=0 | | 8x-4=-68 | | 20-5x+0.15x^2=0 | | 4x-22=50 | | x^3-2x^2+3-2=0 | | 0.10(x+200.00)=100 | | 13+2y=10y-12 | | 62=6g | | 8y-3y+7=87 | | 7x-7[6x-14]=-182 | | 42a^2b+95ab-25b=0 | | -13+14k=k | | 117-3x=15x+19 | | -5x+2[-4x+3]=110 | | 4w+3=(7w-6)(7w-6) | | 12=7c-9 | | 6x^2-47x-46=0 | | 7x+7[x-5]=-147 | | -5(1-5x)+5(-8x-2)=-4x-8x+3 | | 13y+5=5y-5 | | 2(x-4)=4(x-2) | | X-(-2)=6 | | 5(x+3)=3(2x-1) | | 1a+2=(-9) | | -4x-5[-x+10]=-43 | | 6x-8(x+3)=-14 | | 8x+7x-6x=18 | | i=400*0.0013*2 | | -6x+4[-2x+8]=130 | | x^2+39x+47=0 | | -2+8=5-(10p+4) |

Equations solver categories